Temperature Dependence of Hydrogen Solubility and Diffusivity in Hydrogen Permeable Membrane of Pd-Cu Alloy with B2-Type Crystal Structure - Mizuno, Masataka; Watanabe, Shimpei; Yukawa, Hiroshi; Araki, Hideki; Higemoto, Wataru; Matsumoto, Yoshihisa; Sugita, Kazuki; Suzuki, Asuka (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2021)
The temperature dependence of hydrogen solubility and diffusivity of Pd–53mol%Cu alloy membrane with the B2–type crystal structure has been investigated. The hydrogen permeation tests are performed using ultra–pure hydrogen (more than 9N) purified by a Pd–Ag alloy membrane to avoid any influences of impurities. It is found that the hydrogen permeability decreases significantly at low temperatures, especially near room temperature. The time dependence of hydrogen flux is monitored and found that the hydrogen flux decreases gradually during about 4 ~ 5 days after rapid cooling down to room temperature from 623 K.The results of the temperature dependence of the hydrogen permeability are analyzed in view of the consistent description of hydrogen permeation based on hydrogen chemical potential, where the hydrogen flux is proportional to the product of the mobility for hydrogen diffusion, B, and the PCT factor, fPCT. In this study, the pressure–composition–isotherms (PCT curves) for Pd–53Cu alloy with B2 structure are measured for the first time by the in–situ XRD–PCT method, and they are applied to estimate the PCT factors. Then, the temperature dependence of the PCT factor and the mobility for hydrogen diffusion is evaluated. It is revealed that the decrement in hydrogen permeability at low temperatures is mainly attributable to the decrement of the mobility for hydrogen diffusion.According to the positron annihilation experiments, the defects density is considered to be small in Pd–53Cu alloy with the B2 structure even at room temperature, suggesting that the excess Cu atoms in Pd–53Cu alloy occupy the positions of Pd sublattice, at which the Cu atoms form a local BCC–Cu unit. The diffusion of Cu atoms corresponds to the diffusion of BCC–Cu units in the B2 structure. Therefore the diffusion of Cu atoms and the configuration of BCC–Cu units in B2 structure could be a key to understand the gradual transition of hydrogen diffusivity at low temperatures.